Implementasi Program Hafalan Hadis dan Doa dalam Pembentukan Akhlaqul Karimah Siswa - Zara Cherya Pramita; Mahariah (SALIHA: Jurnal Pendidikan & Agama Islam, 2023)
In the present era, there are numerous reports concerning the decline in students’ moral conduct. At SD Swasta Islam Ulun Nuha, there are also students who lack good moral values, albeit not dominating the students population. Thus, it is necessary for the school to find solutions to this problem. This research aims to elucidate: (1) The background for the emergence of the hadith and prayer memorization program, (2) The implementation of the hadith and prayer memorization program, (3) The supporting and inhibiting factors in the implementation of the hadith and prayer memorization program. This study adopts the field research method and utilizes qualitative research with a phenomenological approach. The research findings indicate that: (1) The background for the emergence of the hadith and prayer memorization program stems from the existence of students with poor moral conduct, thus the program aims to shape noble moral conduct in students, (2) The implementation of the hadith and prayer memorization program involves imploying problem-based learning strategies and lecture methods to explain the meanings of the hadiths and prayers. In the practical aspect of memorization, students are guided by teachers, who initially recite the hadiths and prayers in fragments until they are recited in their entirety. Subsequently, they are memorizes collectively, (3) The supporting factors of the program include parental support and students’ anthuasiasm for memorization. The inhibiting factors of the program include variations in students’ potential for memorization and the diverse range of narrators, often leading to forgetfulness among students.